Geographic structure of genetic variation in the Parachute Gecko Ptychozoon lionotum Annandale, 1905 across Indochina and Sundaland with descriptions of three new species - Grismer, L. Lee; Wood, Perry L. Jr.; Grismer, Jesse L.; Quah, Evan S. H.; Thy, Neang; Phimmachak, Somphouthone; Sivongxay, Niane; Seateun, Sengvilay; Stuart, Bryan L.; Siler, Cameron B.; Mulcahy, Daniel G.; Anamza, Tashitso; et al. (Zootaxa, 2019)
An integrative taxonomic analysis of the Ptychozoon lionotum group across its range in Indochina and Sundaland recovers P. lionotum sensu lato Annandale, 1905 as paraphyletic with respect to P. popaense Grismer, Wood, Thura, Grismer, Brown, & Stuart, 2018a and composed of four allopatric, genetically divergent, ND2 mitochondrial lineages. Multivariate and univariate analyses of continuous and discrete morphological and color pattern characters statistically and discretely diagnose each lineage from one another and together, with maximum likelihood and Bayesian inference analyses, provide the foundation for the recognition of each lineage as a new species—hypotheses corroborated with a Generalized Mixed Yule Coalescent species delimitation analysis. Ptychozoon cicakterbang sp. nov. ranges throughout Peninsular Malaysia to Pulau Natuna Besar, Indonesia; P. kabkaebin sp. nov. is endemic to northern and central Laos; and P. tokehos sp. nov. ranges from southern Thailand south of the Isthmus of Kra northward to Chiang Mai, fringing the Chao Phraya Basin and ranging southward through Cambodia to southern Vietnam. Ptychozoon lionotum sensu stricto ranges from northwestern Laos through southern Myanmar to eastern India. The phylogeographic structure within each species varies considerably with P. lionotum s.s. showing no genetic divergence across its 1,100 km range compared to P. cicakterbang sp. nov. showing upwards of 8.2% sequence divergence between syntopic individuals. Significant phylogeographic structure exists within P. tokehos sp. nov. and increased sampling throughout Thailand may require additional taxonomic changes within this species.